Results from Malaysia's 2016 report card on physical activity for children and adolescents - Sharif, Razinah; Chong, Kar Hau; Zakaria, Nur Hadiyani; Ong, Min Lim; Reilly, John J.; Wong, Jyh Eiin; Abu Saad, Hazizi; Poh, Bee Koon (Human Kinetics, 2016)
Background: The 2016 Malaysia Active Healthy Kids Report Card aims to collect, assess, and grade current and comprehensive data on physical activity (PA) and associated factors in Malaysian children and adolescents aged 5 to 17 years. Methods: This report card was developed following the Active Healthy Kids Canada Report Card protocol. The Research Working Group identified the core matrices, assessed the key data sources, and evaluated the evidence gathered for grade assignments. A grade was assigned to each indicator by comparing the best available evidence against relevant benchmark using a standardized grading scheme. Results: Overall Physical Activity, Active Transportation, and Sedentary Behavior were assigned the D grade. The lowest grade of F was assigned to Diet, while School and Government Strategies and Investments were graded higher with a B. Five indicators were assigned INC (incomplete) due to a lack of representative data. Conclusions: The report card demonstrates that Malaysian children and adolescents are engaging in low levels of PA and active commuting, high levels of screen time, and have extremely low compliance with dietary recommendations. More efforts are needed to address the root causes of physical inactivity while increasing the opportunities for children and adolescents to be more physically active.